2013
DOI: 10.1016/j.jbiomech.2013.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Amputee locomotion: Spring-like leg behavior and stiffness regulation using running-specific prostheses

Abstract: Carbon fiber running-specific prostheses (RSPs) have allowed individuals with lower extremity amputation (ILEA) to participate in running. It has been established that as running speed increases, leg stiffness (Kleg) remains constant while vertical stiffness (Kvert) increases in able-bodied runners. The Kvert further depends on a combination of the torsional stiffnesses of the joints (joint stiffness; Kjoint) and the touchdown joint angles. Thus, an increased understanding of spring-like leg function and stiff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 41 publications
1
38
0
1
Order By: Relevance
“…When athletes with transtibial amputations run, they generate peak vertical ground reaction forces (GRFs) with their affected legs that are 2.1 to 3.3 times body weight at speeds of 2.5 m/s to 10.8 m/s [8,18,25,26]. During running, peak resultant GRFs typically occur around mid-stance and are oriented vertically.…”
Section: Introductionmentioning
confidence: 99%
“…When athletes with transtibial amputations run, they generate peak vertical ground reaction forces (GRFs) with their affected legs that are 2.1 to 3.3 times body weight at speeds of 2.5 m/s to 10.8 m/s [8,18,25,26]. During running, peak resultant GRFs typically occur around mid-stance and are oriented vertically.…”
Section: Introductionmentioning
confidence: 99%
“…We calculated k leg as the ratio of F peak and ΔL (the ratio of F peak and Δy for k vert ) between ground contact (initial leg compression phase) and the instant of F peak 11,14,27,28 . Because body mass influences the stiffness 2 , both k leg and k vert were normalized to the subject's body weight (BW), which included the prosthesis.…”
Section: Methodsmentioning
confidence: 99%
“…They found that the vGRF was significantly higher in the able-bodied athletes than in the double amputee sprinter. Similarly, several studies reported that the RSPs would impair force generation and thus likely limit top speeds 12,[14][15][16] .…”
Section: Advantage or Disadvantage?mentioning
confidence: 99%